Perancangan Aplikasi Pembelajaran Kodifikasi Klinis Berbasis Web - Angga Eko Pramono; Nuryati Nuryati; Dian Budi Santoso (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2024)
One of the main competencies of a Health Information Management (HIM) Practitioner is clinical codification skills. The problem that still occurs is the inaccuracy of clinical codification results. One aspect of the cause is human resource competency, specifically lack of knowledge and skills regarding clinical codification rules and procedures. Therefore, developing a web-based clinical codification learning media application is needed to improve HIM Practitioners' knowledge and skills. This research aims to design a web-based clinical codification learning media. The design was carried out from May to September 2023 using the waterfall method. The research subjects were students and lecturers of health information management and HIM practitioners. The research object was the design of web-based learning media. The data were collected using observation, interview, and documentation study methods. This study resulted in a design system that consists of Unified Modeling Language (UML) of use case diagrams and activity diagrams, a database design that consists of database tables and a database relational diagram, as well as user interface displays which are consists of a login display, home/dashboard, modules, and exercises. The design result should proceed as a blueprint for further system prototyping development process.